Complexity galore: 3D cultures, biomechanics and systems medicine at the eighth ENBDC workshop “Methods in Mammary Gland Development and Cancer” - Lloyd-Lewis, Bethan (Breast Cancer Res, 2016)
The ENBDC workshop “Methods in Mammary Gland Development and Cancer” is an established international forum to showcase the latest technical advances in the field. The eighth meeting focused on emerging concepts and technologies for studying normal and neoplastic breast development.